Oscillation Criteria for Linear Neutral Delay Differential Equations of First Order - Fatima N. Ahmed; Rokiah Rozita Ahmad; Ummul Khair Salma Din; Mohd Salmi Md Noorani (Abstract and Applied Analysis)
Some new sufficient conditions for oscillation of all solutions of the first-order linear neutral delay differential equations are obtained. Our new results improve many well-known results in the literature. Some examples are inserted to illustrate our results.